The Relationship between the Availability of Essential Medicines and Outpatient Satisfaction in the Pharmaceutical Installation - Romauli Anna Marbun (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The availability of essential medicines is a critical factor influencing the quality of pharmaceutical services and greatly affects patient satisfaction. A lack of essential medicines can worsen patient conditions and reduce trust in hospital services. Objective: This study aimed to analyze the relationship between the availability of essential medicines and outpatient satisfaction at the Pharmaceutical Installation of Grandmed Hospital Lubuk Pakam. Research Methods: A quantitative approach with a descriptive correlational design was used. A total of 150 outpatients were randomly selected. Data were collected using a questionnaire and analyzed using Pearson correlation tests to assess the strength and direction of the relationship between variables. Results: The findings revealed a strong and statistically significant positive relationship between the availability of essential medicines and patient satisfaction, with a correlation coefficient (r) of 0.76 and a p-value of 0.0001. Patients who received the required medicines reported higher satisfaction levels than those who did not. Conclusion: The higher the availability of essential medicines in the pharmaceutical installation, the greater the patient satisfaction with pharmaceutical services. Hospital management is encouraged to strengthen the procurement and distribution system, improve inventory management, and enhance communication with patients to sustain and improve satisfaction levels.